2016
DOI: 10.1111/tbed.12525
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Tembusu Virus Circulating in Muscovy Ducks in South China

Abstract: Duck Tembusu virus (DTMUV) is an infectious pathogen that can cause epidemics in egg-laying ducks. Here, we isolated and characterized a DTMUV, designated GDLH01, thought to be responsible for the noticeable egg drop in Muscovy duck flocks in South China since 2011. The genome sequence of GDLH01 shared 97-99% homology with other avian-origin Tembusu viruses, and 99.5% homology with the mosquito-borne strain SDMS recently reported in China. Phylogenetic analysis based on the nucleotide sequence of the entire op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The mature virion could be observed by transmission electron microscopy (TEM), having the nucleic acid in the center and an envelope with the diameter of 40 to 60 nm [9]. There is a high homology among various DTMUV strains and other Flaviviruses [10].…”
Section: Introductionmentioning
confidence: 99%
“…The mature virion could be observed by transmission electron microscopy (TEM), having the nucleic acid in the center and an envelope with the diameter of 40 to 60 nm [9]. There is a high homology among various DTMUV strains and other Flaviviruses [10].…”
Section: Introductionmentioning
confidence: 99%
“…TMUV was reported to cause epidemics affecting ducks in China in 2010, leading to huge economic losses and attracting widespread attention (Cao et al, 2011). A wide range of avian species, including geese, chickens, house sparrows, and pigeons, was confirmed to be naturally infected by TMUV (Tang et al, 2013a(Tang et al, , 2015Chen et al, 2014;Yan et al, 2017Yan et al, , 2022Zhu et al, 2022), and infections in human have been demonstrated by serological tests or the presence of RNA (Wolfe et al, 2001;Tang et al, 2013b). Due to the lack of widespread surveillance, the virus is mostly reported in Thailand, Malaysia, and China, with few reports of TMUV in Vietnam (Hamel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Since TMUV was first reported in 2010, it had widely spread in China (Liu et al, 2013;Z. Xie et al, 2014;Yan et al, 2017;Yun et al, 2012;X. Zhou et al, 2016;Zhu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%